Faculty Input in Evaluation for a College with Many Disciplines - David Bellar; Nathan M Roberts; Paula M Montgomery (Academic Chairpersons Conference Proceedings, 2016)
The co-presenters will describe how faculty in one academic unit of a large College combining many academic disciplines were tasked with examining best practices and development of a faculty merit performance evaluation rubric. Perspective on the project will be offered by the initiating School Director, Dean of the College and Associate Dean of the College .
Keywords: Shared Governance; Performance Evaluation; Assessment; Leadership; Faculty Engagement